2020
DOI: 10.1016/j.chom.2020.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Type I and Type III Interferons – Induction, Signaling, Evasion, and Application to Combat COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) is a global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Without approved antiviral therapeutics or vaccines to this ongoing global threat, type I and type III interferons (IFNs) are currently being evaluated for their efficacy. Both the role of IFNs and the use of recombinant IFNs in two related, highly pathogenic coronaviruses, SARS-CoV and MERS-CoV, have been controversial in terms of their protective effects in the host. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
903
0
16

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 793 publications
(990 citation statements)
references
References 77 publications
26
903
0
16
Order By: Relevance
“…To better understand the role of type I interferon signaling we infected both IFNAR -/and IRF3/7 -/and showed that despite similar kinetics of viral clearance, there was significant blunting of ISG response, suggesting that viral replication is resistant to interferon signaling as was previously show with SARS-CoV-1 14 and has been suggested in SARS-CoV-2 given its vast array of interferon antagonists 19 . While endogenous type I interferon signaling seems to have little effect on SARS-CoV-2 replication, it clearly orchestrates a proinflammatory immune response and may cause immunopathology in patients.…”
Section: Discussionmentioning
confidence: 81%
“…To better understand the role of type I interferon signaling we infected both IFNAR -/and IRF3/7 -/and showed that despite similar kinetics of viral clearance, there was significant blunting of ISG response, suggesting that viral replication is resistant to interferon signaling as was previously show with SARS-CoV-1 14 and has been suggested in SARS-CoV-2 given its vast array of interferon antagonists 19 . While endogenous type I interferon signaling seems to have little effect on SARS-CoV-2 replication, it clearly orchestrates a proinflammatory immune response and may cause immunopathology in patients.…”
Section: Discussionmentioning
confidence: 81%
“…The mechanisms of this innate immune system were suggested in the study by Paki and Iwasaki; 44 Interferon (IFN) response is an adaptive form of the immune system and its timing can vary with viral load and/or genetic differences. An early IFN response can lead to rapid viral clearance before its replication, resulting in milder diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Suppression of IFN signaling by SARS-CoV-2 has been reported by several studies 26,27 , possibly explaining only a moderate effect of SARS-CoV-2 infection on dACE2 induction in our experiments. While type I and type III IFNs are barely detectable in COVID-19 patients 28,29 , high levels of IFN-γ have been reported 29,30 . Specifically, a 3'-scRNA-seq analysis showed ACE2 induction by SARS-CoV-2 infection in ciliated epithelia, where high levels of IFN-γ producing immune cells were also detected 5 .…”
Section: Discussionmentioning
confidence: 95%